The Effectiveness of a Program Based on Cognitive Approach and Corrective Feedback in Developing High Institute of Engineering and Technology Students’ EFL Oral Performance, Technical Vocabulary Use and Reducing Their Communicative Apprehension - Muhammad , Badeaa Akl Drwish; Hamdy, Azza Ahmed; Abdelwahab, Amr Fathy (Journal of Neonatal Surgery, 2025)
The current study aimed at developing the High Institute of Engineering and Technology 3rd year students' EFL oral performance, technical vocabulary use and reducing their communicative apprehension using the cognitive approach and corrective feedback. The current study adopted the mixed-method research design. A group of (74) High Institute of Engineering and Technology enrolled in the third year, 10th of Ramadan city, Sharkia Governorate in the academic year 2023/2024 were equally divided into a treatment group (n=37) and non-treatment group (n=37). The data were collected through an EFL oral performance recorded interview, an EFL oral performance checklist, EFL oral performance test, EFL technical vocabulary use test and a communicative apprehension Scale. These instruments were designed by the researcher and approved by a list of jury members in the field of TEFL. They were pre/post-administered to the treatment group before and after teaching the study program. The obtained data were analyzed using the Statistics Package for Social science (SPSS). The study results revealed that there was a statistically significant difference at (0.5) between the mean scores of the treatment group in the pre/post results of oral performance favoring the post results. The finding also revealed that the program based on cognitive approach and corrective feedback had positive effect on developing the High Institute of Engineering and Technology students' EFL oral performance and technical vocabulary use and reducing their communicative apprehension. Consequently, it is recommended to adopt the program based on cognitive approach and corrective feedback as a pivotal approach in teaching EFL oral communicative skills to develop EFL oral performance, technical vocabulary use and reduce communicative apprehension at universities and schools...